The Participation in Ecological Activities and Its Influence on High School Pupils' Attitude towards The Environment: Famagusta Case - Ucisik Erbilen, Suheyla (Ani Yayincilik, 2013)
Problem Statement: Today's arising environmental and global challenges that are originated from mainly human activities (e. g. rapidly increasing world population together with a similarly fast-growing consumption, raw material, energy shortage, and the failure in the balanced distribution of resources, lack of fresh water supplies and various other social problems) are a chain of problems that disrupt the homeostasis in the ecosystem. Specifically the effect over natural habitats is striking. Although the population of Cyprus is not high and the industry is not highly developed, it still faces environmental problems every day. Since human is the most important factor of the pollution, the insemination of the importance of ecology knowledge and sensitivity into young minds is essential to protect the environment for the next generations. Thus, here we state our research problem as; what are the attitudes and behaviors of high school students to the environment in a developing country. The Purpose of the Study: In this study, we aimed to identify the knowledge and behaviors of Central-Famagusta high school pupils towards the environment. We also examined the awareness of students towards the environment according to their age, gender as well as the income and the education levels of their families. Method: We conducted a questionnaire and the Environmental Attitude Scale on 574 high school pupils from two different high school grades. Statistical analyses were done by SPSS 17 statistics program. The frequency (f), means and T test and ANOVA were used to analyze the data. Findings and Results: We found that (1) environmental awareness is not affected by the income level of the family (2) participation into environment-related activities with teachers and friends at school has a positive effect on students (3) students who participate into environmental activities gain the capacity to transform environmental ideas to behavior and at the same time acquire the conscious of warning others that are damaging the environment. Conclusions and Recommendations: Our study aims to understand the environmental awareness and behavior of high school students of different age and gender groups that come from different backgrounds. We found that the most effective way of teaching the importance of environmental and ecological problems to younger minds is to provide them environment-related activities where they can take active roles and hands-on experiences. This should be done in collaboration by pedagogues and teachers starting at the first step of the education system.
Keywords: High school pupil; Environmental behavior; Environmental thinking; Ecology; Famagusta; North Cyprus